Estudio visual de la cultura y tradiciones de la parroquia san Juan de la provincia de Chimborazo para su aplicación en un documental turístico - Pérez Domínguez, Jessica Liset (2016)
The tourist documentaries have turned into one of the means of advertising used to come to the television viewer, for such a motive one sees the need to create advertising effective videos it is to say first, to plan a strategy of the message, which will allow the identification of the benefits, develop a creative concept as it serves to choose the advertising attractive, and this great idea has to become running an ad, which will analyze the selection of advertising media for the advertising program be evaluated regularly and analyzing how the advertising function, allowing us to reach the target and the expectations we all hope will be organized. The design used was inductive, analytical, and descriptive, with compilation of information from owners of tourist agencies of the city Riobamba, Educational Institutions of the parish and its population in general and the parochial Vestry of San Juan. Results: 25% of respondents accounted if they have knowledge of the culture that owns the parish San Juan being in total 94 respondents, while 75% of the population and educational institutions for a total of 281 involved, they determined that if aware of what the culture of the parish. 50% of respondents agreed that the priority for the realization of a tourist documentary is to satisfy needs, while the other 50% determined that the priority is to impact the audience to watch the finished tour documentary. 50% of respondents say that one of the major difficulties that have to make a tour documentary is the lack of professional interest that put the job done editors and project participants; whereas the other 50% say that most difficulty is the lack of trained staff to make the documentary.